EFFECT OF TAX BENEFITS ON THE INCOME TAX COLLECTION - Orellana Ulloa, Milca Naara (2017)
In Ecuador, fiscal policy is directly linked to economic policy, allowing the State to have a collection of taxes to cover public expenditure, this income should be redistributed in the less favored sectors. Given the need to identify the impact of the application of tax benefits used by companies, whether new or already operating, and natural persons who are or not required to keep accounting. There is a need to know the behavior of these Economic sectors, given the various changes that have taken place in the Ecuadorian tax legislation and which have led to an increase or decrease in the collection of Income Tax in the Province of El Oro. For this reason, the main problem has been identified as the need to know which is the economic impact of the tax benefits related to exemptions and exonerations in the payment of Income Tax in the economic sectors in the Province of El Oro in the period 2010-2012. The method used is non-experimental, cross-sectional, obtaining a positive result for the taxpayer, encouraging the productive growth of the country and negative in the collection of income tax.